2001
DOI: 10.12930/0271-9517-21.1-2.32
|View full text |Cite
|
Sign up to set email alerts
|

Style Over Substance Revisited: A Longitudinal Analysis of Intrusive Intervention

Abstract: In a recent report, the authors showed that the academic intervention process, rather than the specific intervention content, was responsible for a short-term influx in at-risk student performance and persistence. Students in varying degrees of academic probation were randomly assigned to one of three intervention strategies that incorporated controlled content but divergent levels of intrusiveness. Results showed that the most intrusive intervention produced higher cumulative grade-point averages and retentio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…This characteristic also relates to Latinos' likely greater acceptance of a more intrusive advisement process. Such an advisement process has previously been demonstrated to be more effective with probationary students in a nondiverse sample (Abelman & Molina, 2001 ;Earl, 1988 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This characteristic also relates to Latinos' likely greater acceptance of a more intrusive advisement process. Such an advisement process has previously been demonstrated to be more effective with probationary students in a nondiverse sample (Abelman & Molina, 2001 ;Earl, 1988 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies with these students have primarily been descriptive of the population or of the corrective strategies that have been attempted with varying levels of success. Probationary students have typically been defined as earning less than a C grade average, and have been found to possess a few characteristics in common including poor academic preparation-sometimes, regardless of high school grades (Earl, 1988 ;Tinto, 1993, Trombley, 2000; low motivation (Abelman & Molina, 2001;Tinto, 1993 ); poor time management (Earl, 1998;Thombs, 1995 ;Tinto, 1993 ); and unused or poor study skills (Astin, 1993 ;Coleman & Freedman, 1996 ;Thombs, 1995 ). Probationary students were also found to possess an external locus of control (Cohen & Brawer, 2002 ;Tinto, 1993 ).…”
Section: Probationary Studentsmentioning
confidence: 99%
“…In their research, Abelman and Molina found that proactive advising success depends on the level of intrusiveness, with greater intrusiveness correlating with better grade point average (GPA) outcomes (Abelman & Molina, 2001Molina & Abelman, 2000). Their longitudinal study largely focused on GPA and retention as success outcomes, two constructs important to institutional reputation and advising-related research.…”
Section: Assessing Student Learning In Advisingmentioning
confidence: 99%
“…Research reveals that students on academic probation typically earn less than a C grade point average [6], have poor academic preparation [7,8] and inadequate time management skills [9][10][11], lack study skills [12,13], and have difficulty in transitioning and adjusting to college life [9,14]. Probationary students also exhibit lower levels of motivation [14,15] and demonstrate an external locus of control [3,9,13] impacting their beliefs about how much control they have in improving their academic situations. "When students are faced with academic demands, the way they approach academic tasks and view themselves can play a significant role in their academic success" [14] (pp.…”
Section: Characteristics Of Probationary Studentsmentioning
confidence: 99%